2006
DOI: 10.1111/j.1468-2982.2005.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Migraine and Atopic Disorders—the Contribution of Pulmonary Function Tests and Immunological Screening

Abstract: This cross-sectional clinical study was conducted in order to explore the relationship between atopic disorders and migraine. We evaluated 186 consecutive patients with migraine. Patients with a history of atopic disorders were compared with the others during headache-free intervals, for their headache characteristics, pulmonary test (PFT) performances and immunological screenings, through appropriate statistical methods. Of the patients with migraine, 77 (41.4%) reported at least one atopic disorder. PFT scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 36 publications
4
59
0
1
Order By: Relevance
“…Although we found that asthma was related to daily headache in general, there is no explicit mechanism to explain this association. By contrast, a mechanism to explain the relationship between asthma and migraine has been suggested; platelet-activating factor and substance P, both of which are closely linked to the pathogenesis of asthma, also play a major role in inducing migraine [12]. Further studies are needed to investigate the mechanism explaining the association between asthma and daily headache.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although we found that asthma was related to daily headache in general, there is no explicit mechanism to explain this association. By contrast, a mechanism to explain the relationship between asthma and migraine has been suggested; platelet-activating factor and substance P, both of which are closely linked to the pathogenesis of asthma, also play a major role in inducing migraine [12]. Further studies are needed to investigate the mechanism explaining the association between asthma and daily headache.…”
Section: Discussionmentioning
confidence: 94%
“…Asthma patients with headache, especially daily headache, may have a lower quality of life than those without headache [10,11]. Although there have been sufficient studies showing an association between asthma and migraine, the relationship between asthma and daily headache has not been clarified [12][13][14][15].…”
Section: Introductionmentioning
confidence: 98%
“…[34][35][36] Migraine has been linked to a hypersensitive immune system. 37 However, Davey and associates 35 claim that the link appears to be independent of allergic mechanisms.…”
mentioning
confidence: 99%
“…Another common feature of asthma and migraine is the presence of atopic characteristics that can be observed in patients. In a previous study, the prevalence of atopy in migraine patients was found to be near that in asthma patients [6].…”
Section: Introductionmentioning
confidence: 99%